2001
DOI: 10.1093/jac/47.5.671
|View full text |Cite
|
Sign up to set email alerts
|

Activities of cholic acid-derived antimicrobial agents against multidrug-resistant bacteria

Abstract: Cationic cholic acid derivatives displayed potent and broad-spectrum activity against multidrug-resistant Gram-negative and -positive bacteria. Specific examples were effective permeabilizers of the outer membranes of many strains of multidrug-resistant Gram-negative bacteria and sensitized these to hydrophobic antibiotics. We also prepared a new cholic acid derivative with improved apparent selectivity for prokaryote membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 4 publications
1
39
0
Order By: Relevance
“…As mimics of AMPs, ceragenins display broad-spectrum activity against Gram-negative and positive bacteria, including activity against drug-resistant organisms [33, [52][53][54]. Studies of bacteria susceptibility to ceragenins has focused on clinical isolates and bacteria, primarily clinical isolates, endemic to specific areas of the human body.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…As mimics of AMPs, ceragenins display broad-spectrum activity against Gram-negative and positive bacteria, including activity against drug-resistant organisms [33, [52][53][54]. Studies of bacteria susceptibility to ceragenins has focused on clinical isolates and bacteria, primarily clinical isolates, endemic to specific areas of the human body.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…At least partial activity described for DS may be expected from disubstituted DS (D2S). DS and D2S (20,22,37) share some structural and functional properties with squalamine, a membrane-active cationic steroid antibiotic (CSA) (34), and some previously described cholic acid antimicrobial derivatives (23,42). Squalamine, first isolated from tissues of the dogfish shark, and its analogues with different polyamines added to the 3-keto group by reductive amination (29) effectively kill different strains of bacteria, but mammals appear not to produce cationic steroids as antimicrobial factors (17).…”
mentioning
confidence: 99%
“…The bactericidal properties of these compounds are due to membrane disruption, and they display a moderate degree of selectivity for prokaryotic over eukaryotic membranes (40). Many cholic acid derivates, such as L-lysine, lysyl-lysine (4), cholic acid with basic amino acids (5,32), guanidine (41), and spermidine (13), were previously characterized as potent antimicrobial agents that kill a wide range of strains, including multidrug-resistant bacteria (42) and fungi (26). In addition to previously described steroidal conjugates (40), we found that D2S displays strong antibacterial activity with low lytic effect on eukaryotic plasma membranes (20) and inhibits the inflammatory response induced by bacterial wall products in vitro.…”
mentioning
confidence: 99%
“…Perturbation of the OM alone has been thought to result in bacterial killing, since immobilized PMB can disrupt the OM (41); however, alternate hypotheses concerning "self-promoted" uptake of the antibiotic and subsequent perturbation of the inner membrane (IM), culminating in bacterial lysis, have also been suggested (11, 64). The recognition that membrane-active antimicrobials have not yet been exploited adequately in the clinic has spurred the search for noncytolytic, selective bacterial membrane-permeabilizing agents, notable examples of which include cationic peptides (18,19) and smallmolecule PMB mimics (12,13,27,44). The use of cationic peptides as therapeutic agents is fraught with several potential problems, including large therapeutic doses (a consequence of high molecular weight), parenteral administration because of the lack of oral bioavailability, immunogenicity, and nonspecific cytotoxicity (60).…”
mentioning
confidence: 99%